2013
DOI: 10.3389/fphar.2013.00044
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition reduces cardiac connexin43 expression and gap junction communication

Abstract: Histone deacetylase inhibitors (HDACIs) are being investigated as novel therapies for cancer, inflammation, neurodegeneration, and heart failure. The effects of HDACIs on the functional expression of cardiac gap junctions (GJs) are essentially unknown. The purpose of this study was to determine the effects of trichostatin A (TSA) and vorinostat (VOR) on functional GJ expression in ventricular cardiomyocytes. The effects of HDAC inhibition on connexin43 (Cx43) expression and functional GJ assembly were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…However, Veenstra and coworkers showed that SAHA also induced Cx43 mRNA reduction in neonatal mouse cardiomyocytes, consistently with the decreased association of Cx43 promoter with RNA Pol II and the increased association with HDACI [25]. In our model, increased acetylation was only evident for proteins with molecular weights ranging from 25 to 130 kDa, while the signals for anti-pan-Ac-K remained stable at molecular weights below 25 kDa, compatible with histones.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, Veenstra and coworkers showed that SAHA also induced Cx43 mRNA reduction in neonatal mouse cardiomyocytes, consistently with the decreased association of Cx43 promoter with RNA Pol II and the increased association with HDACI [25]. In our model, increased acetylation was only evident for proteins with molecular weights ranging from 25 to 130 kDa, while the signals for anti-pan-Ac-K remained stable at molecular weights below 25 kDa, compatible with histones.…”
Section: Discussionsupporting
confidence: 66%
“…3) [25], thus suggesting the hypothesis that electrical stimulation could promote Cx43 acetylation. However, the adjunct of Verapamil 10 μM to SAHA treated HL-1 cells failed to rescue Cx43 localization at appositional membranes (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although DIs are now in clinical use as valuable anticancer therapy, cardiac adverse side effects (39,40) and cardiac hypertrophy (41) have been recently described associated with their use. Thus, the evaluation of their safety and toxicity is of particular relevance for potential therapeutic application in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of 1-5 mg protein, [protein] determined by the Bradford method (Bio-Rad), separated by SDS-PAGE on 10% polyacrylamide gels, blotted onto Immobilon-P membranes (Millipore), and blocked in 5% nonfat milk Tris-buffered saline (TBS), pH 7.4, overnight at 4 C. Membranes were incubated for 3 h at room temperature with rabbit polyclonal antibodies directed against amino acids 363-382 of Cx43 (Sigma, #C6219) (1:10,000 dilution) or against the C-terminal domain of Cx40 (Invitrogen, #36-4900) (1:1000 dilution). 32 Blots were rinsed repeatedly in TBS and incubated for 1 h at room temperature with a peroxidase-conjugated goat anti-rabbit IgG secondary antibody (Jackson) (Cx43, 1:5,000 dilution; Cx40, 1:5000 dilution, all in 5% nonfat milk TBS, pH 7.4). Immunoblots were developed with ECL Plus chemifluorescent reagents (GE Healthcare) and quantified using a STORM Phosphoimager.…”
mentioning
confidence: 99%
“…All results are expressed relative to GAPDH and a cellular RNA sample without reverse transcription was run as a negative control to test for genomic DNA. 31,32 Immunoblot analysis Cell homogenates were harvested by scraping in ice cold phosphate-buffered saline containing a Roche mini-EDTA-free protease inhibitor tablet (per 5 ml) and 1 mM phenylmethylsulfonyl fluoride. The samples were centrifuged at 10,000 rpm for 2 min and the pellets resuspended and lysed by sonication in 25-100 ml 50 mM Tris-HCl (pH 8.0) containing 150 mM NaCl, 1% Triton X-100, 0.02% sodium azide, 50 mM sodium fluoride, 0.5 mM sodium orthovanadate, and one Roche mini EDTA-free protease inhibitor tablet.…”
mentioning
confidence: 99%